Dancing Between Neoliberal and Nordic: Lifelong Learning in South Korea - Jinhee Choi; Fred M Schied (Adult Education Research Conference, 2016)
The paper argues that the South Korean model is neither Nordic nor Neoliberal as many have claimed. The South Korean model may serve as a model for other Asian countries.
Keywords: South Korean lifelong learning; neoliberal; Nordic